PERAN KOMITMEN ORGANISASI SEBAGAI MEDIATOR PENGARUH ETIKA KERJA ISLAM TERHADAP SIKAP PADA PERUBAHAN - Andriyanto, Irsad; Haerudin, Haerudin (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
The aim of this this study is to uncover the impact of Islamic Work Ethics on Attitude toward Change trough organizational commitment as mediating variable. CEO of BPRS (Bank Pembiayaan Rakyat Syariah) in Indonesia was asked to express their opinion about the statements in the questionaire. Structural Equation Modelling (SEM) was used to analyze the complect relationship in the model aided by Visual Partial Least Square (VPLS) software.The results indicated that there is no direct effect from Islamic work ethics on attitude toward change. The interested finding in this research showed that organizational commitement mediated Islamic work ethic in only one dimension, affective commitment. The implication of this research is that management need to develop the application of Islamic work ethic to increase organizational commitment, so that can bring up attitude of employees ready to face change even if only on affective dimension only.